2017
DOI: 10.1097/mph.0000000000000943
|View full text |Cite
|
Sign up to set email alerts
|

Children and Adolescent Hodgkin Lymphoma in Argentina: Long-term Results After Combined ABVD and Restricted Radiotherapy

Abstract: The strategy of avoiding RT for LR and IR patients that responded completely to ABVD chemotherapy achieved very good results. For the HR group, the combination of 6 cycles of ABVD and Low-dose involved field radiotherapy was efficacious with similar good results. Nearly half of the patients could be cured without RT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 20 publications
1
4
0
1
Order By: Relevance
“…Faizan et al [7] from Pakistan used same treatment protocol and reported very similar 5-years OS and EFS as 92 % and 84 % respectively. Other studies from developing countries reported similar results [7][8][9][10][12][13][14]19,20]. (Summarized in Table 3).…”
Section: Discussionsupporting
confidence: 68%
“…Faizan et al [7] from Pakistan used same treatment protocol and reported very similar 5-years OS and EFS as 92 % and 84 % respectively. Other studies from developing countries reported similar results [7][8][9][10][12][13][14]19,20]. (Summarized in Table 3).…”
Section: Discussionsupporting
confidence: 68%
“…In some pediatric patients with CHL, the ABVD regimen (doxorubicin, bleomycin, vinblastine, and dacarbazine) may be considered. [35][36][37][38][39] The panel recommends referring to the NCCN Guidelines for Hodgkin Lymphoma in adults (available at NCCN.org) to review relevant data and context.…”
Section: Low-risk Chlmentioning
confidence: 99%
“…As recommended for low-risk CHL, the ABVD regimen may be considered for some pediatric patients. [35][36][37][38][39] The panel recommends referring to the adult NCCN Guidelines for Hodgkin Lymphoma to review relevant data and context.…”
Section: Nccn Recommendations For Intermediate-risk Chlmentioning
confidence: 99%
See 1 more Smart Citation
“…Количество введений этопозида в каждом курсе увеличилось с 4 до 5 (ОЕРА), таким образом, кумулятивная доза за 2 курса составила 1250 мг/м 2 . Однако это значение осталось ниже критической кумулятивной дозы этопозида в 2000 мг/м 2 , приводящей впо-1 О р и г и н а л ь н ы е и с с л е д о в а н и я || O r i g i n a l s t u d i e s следствии к высокому риску развития вторичного острого миелобластного лейкоза [10,12,13]. В целях исключения прокарбазина курс СОРР был модифицирован в COPDAC с применением дакарбазина.…”
Section: Introductionunclassified